2011
DOI: 10.5194/cp-7-1415-2011
|View full text |Cite
|
Sign up to set email alerts
|

The role of orbital forcing, carbon dioxide and regolith in 100 kyr glacial cycles

Abstract: Abstract. The origin of the 100 kyr cyclicity, which dominates ice volume variations and other climate records over the past million years, remains debatable. Here, using a comprehensive Earth system model of intermediate complexity, we demonstrate that both strong 100 kyr periodicity in the ice volume variations and the timing of glacial terminations during past 800 kyr can be successfully simulated as direct, strongly nonlinear responses of the climate-cryosphere system to orbital forcing alone, if the atmos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
150
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(202 citation statements)
references
References 49 publications
10
150
1
Order By: Relevance
“…However, our model results also illustrate that orbital forcing alone was not sufficient, and that the ∼ 100 ppmv CO 2 rise needs to be taken into account to explain the fast and full retreat of the North American and Eurasian ice sheets during the deglaciation. This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, our model results also illustrate that orbital forcing alone was not sufficient, and that the ∼ 100 ppmv CO 2 rise needs to be taken into account to explain the fast and full retreat of the North American and Eurasian ice sheets during the deglaciation. This supports previous model studies, which have identified GHG variations as an important contributor to Pleistocene glacial cycles (Gallée et al, 1992;Yoshimori et al, 2001;Ganopolski and Calov, 2011;AbeOuchi et al, 2013). And the results emphasize how important it is to identify the mechanisms responsible for the orbitalscale modulation of atmospheric CO 2 concentrations (Kohfeld and Ridgwell, 2009;Tagliabue et al, 2009;Chikamoto et al, 2012;Menviel et al, 2012;Brovkin et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the reduction of dust deposition rates on snow and ice during the deglaciation may have been a negative feedback process. Previous studies with the coupled ice sheet-climate model CLIMBER-2, including a dust model, indicated that aeolian dust feedbacks played an important role during glacial cycles Ganopolski and Calov, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, temporal development of ice-age cycles provides critical information about the nature of long-term climate cooling over the past few million years, in response to CO 2 reduction and interactions among ice, land cover, and climate (e.g., Clark et al, 2006;K€ ohler and Bintanja, 2008;de Boer et al, 2010de Boer et al, , 2012Hansen et al, 2013). Third, variable amplitude of individual ice ages helps to determine the relationship between climate change, astronomical climate forcing cycles, and climate feedbacks on timescales of 10se100s of kiloyears (e.g., Oglesby, 1990;Imbrie et al, 1993;Raymo et al, 2006;Colleoni et al, 2011Colleoni et al, , 2016Ganopolski and Calov, 2011;Carlson and Winsor, 2012;Abe-Ouchi et al, 2013;Hatfield et al, 2016;Liakka et al, 2016). Fourth, the size and spatial distribution of land ice during past glacials determines crustal rebound processes when ice masses melt, which in turn affects sea-level reconstructions for subsequent interglacials.…”
Section: Introductionmentioning
confidence: 99%